2017
DOI: 10.1111/crj.12612
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pulmonary artery to ascending aorta ratio in chronic obstructive pulmonary disease

Abstract: Our study showed that PA/A was related with the number of hospitalizations and the total number of exacerbations due to COPD in 1 year. However, there was no relationship between PA/A and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The pulmonary artery to ascending aorta diameter ratio (PA:A) has been evaluated thoroughly in numerous studies analyzing cardiac magnetic resonance (CMR) and computed tomography (CT) data. The ratio was able to detect patients with PH [2][3][4][5][6], it correlated with hemodynamics [7][8][9][10], and it was predictive for morbidity [11][12][13] and mortality [14][15][16][17]. Different cutoffs for PA:A have been suggested to identify PH, depending on the methodology (CMR or CT), ranging from 0.83 to >1 [2,14,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary artery to ascending aorta diameter ratio (PA:A) has been evaluated thoroughly in numerous studies analyzing cardiac magnetic resonance (CMR) and computed tomography (CT) data. The ratio was able to detect patients with PH [2][3][4][5][6], it correlated with hemodynamics [7][8][9][10], and it was predictive for morbidity [11][12][13] and mortality [14][15][16][17]. Different cutoffs for PA:A have been suggested to identify PH, depending on the methodology (CMR or CT), ranging from 0.83 to >1 [2,14,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Iliaz et al ( 18 ) showed, on 156 patients hospitalized for COPD exacerbations, that PA/A ratio positively correlated with the number of hospitalizations due to COPD in one year. In another study, PA/A>1 was significantly related to the number of exacerbations ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased MAP/AO ratio, a very simple index measured on a routine CT acquisition, has been shown linked to an increased risk of exacerbation in COPD108,111,117 and a lower 6-mins walk distance 118. Mortality in COPD population was also correlated to MAP/AO ratio in some reports115,119 but not in others 108,110. Interestingly, this ratio was not correlated to mortality in the general population 119.…”
Section: Central Vesselsmentioning
confidence: 97%
“…In COPD, a correlation has been shown between mPAP and enlargement of the main pulmonary artery truncus (MAP) diameter, and this increase is observed when MAP is normalized by ascending aorta diameter (MAP/AO) 86,107110. Usually, normalization is made on ascending aorta107,108,111,112 (see Figure 3) but it has also been done on descending aorta 21. Usually, MAP widest dimension is measured on axial CT images, on inspiratory acquisition, at bifurcation level, and, AO is measured on the same image 107,108,111,112.…”
Section: Central Vesselsmentioning
confidence: 99%
See 1 more Smart Citation